Yeast Isolation for Bioethanol Production - EKA RURIANI; TITI CANDRA SUNARTI; ANJA MERYANDINI (HAYATI Journal of Biosciences, 2012)
We have isolated 12 yeast isolates from five different rotten fruits by using a yeast glucose chloramphenicol agar (YGCA) medium supplemented with tetracycline. From pre-screening assay, four isolates exhibited higher substrate (glucose-xylose) consumption efficiency in the reaction tube fermentation compared to Saccharomyces cerevisiae dan Saccharomyces ellipsoids as the reference strains. Based on the fermentation process in gooseneck flasks, we observed that two isolates (K and SB) showed high fermentation efficiency both in sole glucose and mixed glucose-xylose substrate. Moreover, isolates K and SB produced relatively identical level of ethanol concentration compared to the reference strains. Isolates H and MP could only produce high levels of ethanol in glucose fermentation, while only half of that amount of ethanol was detected in glucose-xylose fermentation. Isolate K and SB were identified as Pichia kudriavzeevii (100%) based on large sub unit (LSU) ribosomal DNA D1/D2 region.